O direito de acesso à justiça e a litigância excessiva: análise da (in)existência de abusos no comportamento do maior litigante brasileiro o Instituto Nacional de Seguro Social - Luiza Berlini Dornas Ribeiro (2016)
This dissertation studies the obstacles to access to justice, especially the excessive litigation of some big and outstanding procedural actors. The excessive litigation interferes therefore in the duration of processes, causing harm in different ways to the parties involved, but more hardly supported by hyposufficient of the demand. After the analysis of this topic, the dissertation delves into a case study of the largest litigant in the Brazilian procedural system, which is the National Institute of Social Security. All data provided by the Report INSS in Numbers and all initiatives and programs targeting demand reduction introduced by the INSS Federal Attorney were taken into account. Thus, from the consideration of these data, the dissertation sought to examine whether the INSS, even being the largest litigant figure, has adopted initiatives that would not be compatible with an improper posture in the use of access to justice, which is why it would not be possible to conclude the existence of an abuse. Another analysis was about the ability of the INSS to establish the existence or lack of incentive to judicialization of conflict. Finally, the INSS structure was examined in order to check if it has legal link with considerable portion of society or not, which may reflect in its position in the ranking of the biggest litigants.